Kemampuan Pembuktian Matematika Mahasiswa: Systematic Literature Review - Wardani, Putri; Hasanah, Rusi Ulfa; Rifa’i, Muhammad (LANCAH: Jurnal Inovasi dan Tren, 2024)
The aim of this research is to find out how big students' mathematical proof abilities are. Recently, we can see that many students majoring in mathematics are experiencing difficulties in proving mathematics, whether solved directly or indirectly. This research uses a Systematic Literature Review taken from several journals published 2018-2023. The results of the research show that students' mathematical proof has not been achieved as a whole. Because some students do not know the basics of mathematical concepts, the proof steps cannot be completed correctly. However, some of the students who have high abilities can complete it correctly, it's just that the work is not done systematically.